Does country governance and bank productivity Nexus matters? - Kamarudin, Fakarudin; Mohamad Anwar, Nazratul Aina; Md. Nassir, Annuar; Sufian, Fadzlan; Tan, Khar Mang; Iqbal Hussain, Hafezali (Emerald Group Publishing Ltd, 2024)
Indexed by WOS/ Scopus